SEROPREVALENCIA DEL Toxoplasma gondii EN BORREGAS DE UNA EMPRESA GANADERA DE LA SIERRA CENTRAL - Caldas J., Patricia (2006)
Toxoplasma gondii is an intracellular parasite of worldwide distribution that causesreproductive disorders in animals and man. Warm-blooded animals constitute theintermediate hosts, get tissue cysts and disseminate the disease when contaminate thepasture with feces containing oocysts. Domestic and wild feline are the definitive hosts.The objective of the study was to determine the seroprevalence of T. gondii in ewesbelonging to a commercial farm located in the Central Highlands of Junín, Peru, using theIndirect Immunofluorescent Antibody Test (IFAT). A total of 387 sera were collected fromewes of various ages at shearing time in March 2002. The detected seroprevalence was65.9 ± 4.7% (255/387). Seroprevalence increased according to age (p<0.05).